2011
DOI: 10.1002/chem.201100930
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, and Glutathione Peroxidase‐Like Activity of Amino Acid Containing Ebselen Analogues and Diaryl Diselenides

Abstract: The synthesis of some ebselen analogues and diaryl diselenides, which have amino acid functions as an intramolecularly coordinating group (Se···O) has been achieved by the DCC coupling procedure. The reaction of 2,2'-diselanediylbis(5-tert-butylisophthalic acid) or the activated ester tetrakis(2,5-dioxopyrrolidin-1-yl) 2,2'-diselanediylbis(5-tert-butylisophthalate) with different C-protected amino acids (Gly, L-Phe, L-Ala, and L-Trp) afforded the corresponding ebselen analogues. The used precursor diselenides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
41
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(51 citation statements)
references
References 80 publications
5
41
0
Order By: Relevance
“…The GPx activity of the hybrid was determined using the coupled reductase assay, which resulted in a catalytic rate of k cat = 0.022 ± 0.003 m – 1 s –1 (Figures S21). By way of comparison, for ebselen alone we obtained a catalytic rate of k cat = 0.02 ± 0.01 m – 1 s –1 (Figure S22), being in accordance with the literature value ( k cat = 0.0216 m – 1 s –1 ) . Thus, as we could experimentally observe the SOD and GPx activity of the two bioactive units remains unchanged upon their chemical coupling.…”
Section: Resultssupporting
confidence: 89%
“…The GPx activity of the hybrid was determined using the coupled reductase assay, which resulted in a catalytic rate of k cat = 0.022 ± 0.003 m – 1 s –1 (Figures S21). By way of comparison, for ebselen alone we obtained a catalytic rate of k cat = 0.02 ± 0.01 m – 1 s –1 (Figure S22), being in accordance with the literature value ( k cat = 0.0216 m – 1 s –1 ) . Thus, as we could experimentally observe the SOD and GPx activity of the two bioactive units remains unchanged upon their chemical coupling.…”
Section: Resultssupporting
confidence: 89%
“…[10,11] Av ariety of derivatives of the selenacycle have been prepared [12][13][14] and evaluated for their capacity to mimic the natural enzymes. [10,11] Av ariety of derivatives of the selenacycle have been prepared [12][13][14] and evaluated for their capacity to mimic the natural enzymes.…”
mentioning
confidence: 99%
“…In 2011, Selvakumar et al reported the synthesis of some diaryl diselenides bearing amino acid functions, intramolecularly coordinating the selenium atom [169]. These compounds were prepared by reacting 2,2'-diselanediyldibenzoic acid with C-protected amino acids using DCC coupling procedures.…”
Section: Amide-based Mimics: Getting Closer and Closer To The Structumentioning
confidence: 99%
“…Interestingly, the results for L-and D-derivatives were very similar, suggesting that, at least in this kind of experimental model, the chirality does not play a relevant role on catalysis. The authors also described the preparation of more hindered diselenides which anyway had low solubility issues and were thus discarded [169]. Nascimento et al carried out a more comprehensive study on amide-based aromatic and aliphatic diselenides, attempting to build a preliminary Structure-Activity Relationship (SAR) [170].…”
Section: Amide-based Mimics: Getting Closer and Closer To The Structumentioning
confidence: 99%